Emotional Salespeople: customer orientation and emotional intelligence - dos Santos, Agnaldo Antonio; Dornelles, Marcos; Crispim, Sergio Feliciano (Revista de Negócios, 2020)
Customer orientation is recurrent in academic research because it enables more effective value creation for customers and shareholders. In this context, this research investigates an unexplored topic, which is the relationship between the emotional intelligence of salespeople and their customer orientation. In a sample of 167 Brazilian salespeople, two validated scale were used, but rarely applied together: (a) Saxe and Weitz Sales Orientation and Customer Orientation Scale (SOCO); (b) Wong and Law Emotional Intelligence Scale (WLEIS). It was concluded with the structural equation model developed that the percentage of customer orientation variability explained by the model is 12% and that for each increase in standard deviation of total emotional intelligence, customer orientation increases by .35 standard deviation, that emotional intelligence is greater in older salespeople, and that emotional intelligence varies according to the economic sectors of salespeople.